Determinants of Illegal Lending Engagement in Indonesian Rural Areas - Ascaryan Rafinda; Hasan Al Jafa; Agus Suroso; Putri Purwaningtyas; Muhammad Farid Alfarisy; Kiky Srirejeki (Universitas Pendidikan Ganesha, 2024)
This research aims to identify the factors that influence individuals to engage in illegal lending in rural Indonesian areas. Specifically, the study examines the roles of financial knowledge and economic pressure in this decision-making process. Data were collected from 246 participants through both online and paper-based questionnaires. The hypotheses were tested using probit analysis. The findings reveal that financial literacy levels do not significantly affect illegal lending behavior, whereas economic pressure has a significant impact on the decision to engage in illegal lending. These results suggest that efforts to reduce illegal lending should focus on alleviating economic pressures faced by people in rural areas. By addressing the underlying economic conditions that drive individuals toward illegal lending, it is possible to mitigate this behavior and promote more sustainable financial practices. This research contributes to the understanding of illegal lending dynamics and offers valuable insights for policymakers and financial educators aiming to improve financial stability and reduce reliance on illegal lending in rural communities.